Determinasi Kepuasan Pelanggan dan Karakteristik Sosial Ekonomi terhadap Willingness To Pay untuk Air Siap Minum di Perumda Tirtanadi Medan - Munthe, Mirian Jacquiline; Charloq, Charloq; Thoha, Achmad Siddik (JURNAL ILMIAH EDUNOMIKA, 2024)
Under the Sustainable Development Goals (SDGs), one of the key targets is to ensure the availability and sustainable management of water and sanitation for all, with the goal of achieving universal and equitable access to safe and affordable drinking water for the entire global population. To implement the development of ready-to-drink water systems to house connections, it is important to ensure that people are willing to pay the cost. This study aims to evaluate the influence of customer characteristics and satisfaction on Willingness To Pay (WTP) in the development of ready-to-drink water in Perumda Tirtanadi Medan services. WTP analysis is influenced by customer characteristics such as number of family members, type of employment, education level, income, and house size. In addition, customer satisfaction with the quality of drinking water already available in several public facilities in Medan City was also analyzed to understand its influence on Willingness To Pay. Customer satisfaction factors are influenced by average water usage, monthly water account payment fees, clarity, odor, taste, color, water discharge and frequency of water flow. The methodology used included multiple linear regression analysis, classical assumption testing, and reliability analysis. The results of the analysis show that WTP is positively and significantly influenced by customer characteristics and customer satisfaction. This analysis is expected to provide guidance for Perumda Tirtanadi in developing ready-to-drink water to house connections in Medan City. Keywords: Willingness To Pay; Perumda Tirtanadi; customer characteristics; customer satisfaction